Gender Perspective on Impact of Disasters: A Study of Sarawal Rural Municipality, Nawalparasi West, Nepal - Aryal, Pitambar; Gangal, Meenu; Karki, Tej Bahadur (Nepal Journal of Multidisciplinary Research, 2025)
Background: Nepal is highly susceptible to various types of natural disasters, with approximately 90% of its population at risk of experiencing multiple hazards. The country ranks 30th in terms of flood risk, with hilly regions prone to landslides and lowland plains frequently affected by floods. Each year, disasters such as floods, landslides, fires, heat waves, cold waves, and epidemics cause significant loss of lives and livelihood assets. Given the critical role of gender in disaster vulnerability, it is essential to analyze gender-specific perspectives on disaster risk and resilience. Objective: The study aims to explore gender roles and their associated vulnerabilities in disaster events. By examining the perceptions of males and females regarding different disaster-related variables, the research seeks to provide insights into gender-based differences in disaster preparedness, response, and resilience-building efforts. Methods: A quantitative study was conducted in Sarawal Rural Municipality of Nawalparasi West, Nepal. A total of 428 respondents were selected through random sampling, comprising 311 males and 117 females. The study employed six major disaster variables as defined by the United Nations International Strategy for Disaster Reduction (UNISDR) to analyze gender perspectives critically. Statistical methods were used to assess the association between gender and disaster perception. Findings: The study revealed a significant association between gender and disaster perceptions. Males and females demonstrated differing views on disaster risks, preparedness, and coping mechanisms. Understanding these gender-specific differences can help determine levels of vulnerability, identify associated risks, and enhance the coping capacities of different groups. Conclusion: The findings emphasize the need to incorporate gender perspectives into disaster-related research and resilience-building initiatives. Addressing gender-based vulnerabilities can lead to more effective disaster preparedness and response strategies, ultimately improving community resilience. Novelty: This study provides empirical evidence on the gendered dimensions of disaster perception in Nepal, highlighting the importance of integrating gender considerations into disaster risk management. By focusing on a rural municipality, the research offers localized insights that can inform policy and program development for gender-inclusive disaster resilience planning.